SERVICE DEVELOPMENT MODEL OF RECRUITMENT HONORARY WORKERS AT BKD (BADAN KEPEGAWAIAN DAERAH) DISTRICT BANJARNEGARA - Mariana Kristiyanti (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Recruitment is a series of the activity of looking and lure applicants working with motivation, the ability, expertise, and knowledge needed to cover of the identified in planning employmen. In the recruitment process for and selection employees in the region, having standardization different adjusted to the needs of their respective regions. Planning in the management of civil servants is one of the main function of human resources management that contains systematic about demand and supply employees to the future. Procurement employees in the management of civil servants is process of activities to fill formation empty of the quota removal of CPNS (a candidate civil servants) in the kabupaten banjarnegara, Make the district government raised honorer workers to able to meet a need employees in the district Banjarnegara. Problems appear due to the interest of the community to function in honorary workers in the district Banjarnegara. The practice of corruption in the appointment of honorary workers cpns dyeing process recruitment banjarnegara candidates in the district. From trouble recruitment honorary workers above, it was needed model service recruitment useful to anticipate problems in the service of recruitment honorary workers in district banjarnegara.An analysis of the used was qualitative data analysis, and object research taken is in district Banjarnegara, while the data technique uses the interview, observation and kuisioner. Keywords : Recruitment , Honorary Workers , Civil Servant Candidates (CPNS) , Badan Kepegawaian Daerah (BKD)